Impact of supercritical carbon dioxide on the frictional strength of and the transport through thin cracks in shale - Talal Al Shafloot; Arjun Kohli; Tae Wook Kim; Anthony R. Kovscek (Journal of Rock Mechanics and Geotechnical Engineering)
Understanding the mechanical and transport behavior of thin (i.e. small aperture) cracks slipping under supercritical carbon dioxide (sc-CO2) conditions is essential to evaluate the integrity of sealing formations with buoyant sc-CO2 below and the success of waterless fracturing. The two major items of interest in this work are frictional strength and permeability change of the crack. We used a triaxial cell that permits in situ visualization to conduct and monitor slippage along the faces of narrow cracks subjected to triaxial stresses. Such cracks are analogs to small geological faults. We tested carbonate-rich, 1-inch diameter Wolfcamp shale samples that are saw cut 30° to vertical to create a thin crack. Friction coefficients ranged from about 0.6 to 0.8 consistent with expectations for brittle rocks. The sc-CO2 generally did not alter friction coefficient over the time scale of experiments. From a transport perspective, saturating cracks with sc-CO2 substantially decreased permeability of the crack by 26%–52%, while slip resulted in a variety of permeability responses. Overall, the combined impact of sc-CO2 saturation and slip reduced fault permeability for all tests. Our observations support the notion that the sealing capacity of some caprocks improves when saturated with sc-CO2 and that some slip of small fractures is not necessarily detrimental to caprock integrity.